Regulation of Cardiac-Specific Proteins Expression by Moderate-Intensity Aerobic Exercise Training in Mice With Myocardial Infarction Induced Heart Failure Using MS-Based Proteomics - Mi, Shouling; Jiang, Hao; Zhang, Lei; Xie, Zhonglei; Zhou, Jingmin; Sun, Aijun; Jin, Hong; Ge, Junbo (Frontiers in Cardiovascular Medicine, 2021)
This study aims to systematically reveal the changes in protein levels induced by regular exercise in mice with ischemic-induced heart failure (HF). Aerobic exercise training for the ischemic-induced HF mice lasted for 4 weeks and then we used the liquid chromatography-mass spectrometry method to identify and quantify the protein profile in the myocardium of mice. As a whole, 1304 proteins (597 proteins up-regulated; 707 proteins down-regulated) were differentially expressed between exercise group and sedentary group, including numerous of proteins related to energy metabolism. The significant alteration of the component (E1 component subunit alpha and subunit beta) and the activity-regulating enzyme (pyruvate dehydrogenase kinase 2 and pyruvate dehydrogenase kinase 4) of pyruvate dehydrogenase complex and poly [ADP-ribose] polymerase 3, a nicotinamide adenine dinucleotide(+)-consuming enzymes, were further verified in targeted analysis. Generally, this proteomics profiling furnishes a systematic insight of the influence of aerobic exercise on HF.